Personal Data Protection Policy in Law Number 27 of 2022 in Facing the Digital Era in Indonesia - Salwa Salsabila, Sopiya (Edusight International Journal of Multidisciplinary Studies, 2024)
The objective of this research is to further map out the policies on personal data protectionin the face of the digital era in Indonesia. This research employs a quantitative methodsourced from legal documents such as laws, journals, and articles. The use of informationtechnology across various sectors in Indonesia necessitates comprehensive legal protectionpolicies to ensure the safeguarding of personal data. In this effort, regulations on personaldata protection are governed by Law Number 27 of 2022 concerning Personal DataProtection, which addresses various aspects of personal data protection endeavored by theGovernment. However, in practice, this law still has several weaknesses that may lead toless than optimal personal data protection for the public. Problematic issues includediscussions on personal data processing, which can currently be conducted by variousstakeholders without legal permission. Additionally, there are weaknesses in the rights ofdata subjects and their implementation. Therefore, these aspects require governmentattention.